THE SIGNIFICANCE OF USING IDIOMS AND COLLOCATIONS IN ENGLISH AND UZBEK DANCE TERMINOLOGY (Scientific journal of the Fergana State University, 2024)
This article investigates the significance of idioms and collocations in the dance terminologies of English and Uzbek languages. It begins with a clear definition of idioms as fixed expressions that convey meanings beyond the literal interpretations of their individual components. By highlighting how idioms function as stable linguistic units with integrated meanings, the study demonstrates their role in enriching the technical and expressive language of dance. The analysis covers a range of idiomatic expressions and collocations from both English and Uzbek dance terminologies, illustrating their metaphorical and evocative qualities. Examples from English, such as «break a leg» and «dance up a storm,» are contrasted with Uzbek phrases like “balletni to‘g‘ri bajarish” and «xalq raqsi,» showing how each reflects the unique cultural contexts and technical aspects of dance in their respective languages. The article underscores the importance of these idiomatic expressions in capturing the dynamic and expressive nature of dance, enhancing communication within the dance community, and deepening the understanding and appreciation of dance as an art form.